Protocolos De Eutanasia Compasiva Como Herramienta Validada Y Homologada Por La Universidad Antonio Nariño Para Uso Rutinario En La Práctica Clínica De Pequeños Y Grandes Animales (2023)
Due to the evident increase in interest and importance that is given to a bioethical consideration and that these extend to all living beings, in special topics such as animal welfare, due to the links that have developed and strengthened especially between pets and humans, coming to be considered important members of the modern family, this places more importance on how they live and are treated, including how they should die. This interest is not focused solely on animals with which people frequently strengthened affective ties, but towards all forms of life in general, therefore, a concern has also developed in people that leads them to avoid, in the as far as possible, the necessary suffering in the dying animal, in the sacrifice of animals dedicated to human food and research.